2018
DOI: 10.1152/ajpregu.00158.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise cardiac magnetic resonance imaging: a feasibility study and meta-analysis

Abstract: Cardiac stress testing improves detection and risk assessment of heart disease. Magnetic resonance imaging (MRI) is the clinical gold-standard for assessing cardiac morphology and function at rest; however, exercise MRI has not been widely adapted for cardiac assessment because of imaging and device limitations. Commercially available magnetic resonance ergometers, together with improved imaging sequences, have overcome many previous limitations, making cardiac stress MRI more feasible. Here, we aimed to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 64 publications
5
36
0
Order By: Relevance
“…The haemodynamic response to exercise demonstrated a minimal change in LVEDV and a rise in LVSV driven by a fall in LVESV during exercise, which is in keeping with a recent Ex-CMR meta-analysis of 16 Ex-CMR studies [31]. Indeed, our study demonstrated a non-significant decrease in LVEDV with exercise as was demonstrated by the majority of Ex-CMR studies in the Ex-CMR meta-analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The haemodynamic response to exercise demonstrated a minimal change in LVEDV and a rise in LVSV driven by a fall in LVESV during exercise, which is in keeping with a recent Ex-CMR meta-analysis of 16 Ex-CMR studies [31]. Indeed, our study demonstrated a non-significant decrease in LVEDV with exercise as was demonstrated by the majority of Ex-CMR studies in the Ex-CMR meta-analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Using the regression equations of cardiac output against VO 2 in Figure for both methods, at a normal resting VO 2 of 300 mL/min, cardiac output by impedance cardiography would be 5.1 L/min, while that by dye dilution would be only 4.1 L/min. A similar calculation from the Charloux et al paper (their Figure ) estimates cardiac output at this VO 2 would be 6.3 L/min, while that from Bogaard et al (their Figure ) estimates cardiac output would be 4.7 L/min. Taken together with the relatively high body mass of the subjects in our study of 77.0 kg, these calculations suggest that the impedance‐based values in our study may be more accurate than those derived from dye dilution.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have indicated that both techniques offer reliable and valid determinations of cardiac output and are accurate to within 5%‐10% at rest and during exercise . Nowadays, cardiovascular magnetic resonance imaging (CMR) is generally considered the clinical gold standard for quantitative assessment of right and left ventricular dimensions and global systolic function at rest providing a surrogate measure of cardiac output in healthy and diseased . CMR can noninvasively obtain stroke volume and cardiac output from both the pulmonary and systemic circulation, using either cine imaging of the ventricles or flow imaging in the aorta and pulmonary trunk.…”
Section: Strengths Limitations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Submitted 2 January 2019; accepted in final form 28 January 2019 REPLY: We thank LaFountain et al (2) for their interest in our recent manuscript on exercise cardiac magnetic resonance imaging (1). The principle critique raised by the authors centers on the appropriateness of our inclusion of their study in our meta-analysis of the normative cardiac response to supine exercise MRI.…”
mentioning
confidence: 99%